Time trends of PCDDs, PCDFs, DL-PCBs, and NDL-PCBs in Italian women from biomonitoring studies. (December 2022) - Miniero, Roberto; di Domenico, Alessandro; Abate, Vittorio; Abballe, Annalisa; Dellatte, Elena; De Filippis, Stefania; De Luca, Silvia; Ferri, Fabiola; Fulgenzi, Annarita; Iacovella, Nicola; Iamiceli, Annalaura; Ingelido, Annamaria; et al.
Abstract: A number of biomonitoring investigations were carried out in Italy between 2000 and 2018 by the Unit of Human Exposure to Environmental Chemicals of the Italian National Institute of Health (Rome). The investigations were characterized by different features (case-control or cross-sectional studies, participants from impacted or no impacted areas, etc), but despite the differences, it was possible to study the time trends of Σ7 (PCDDs), Σ10 (PCDFs), Σ12 (DL-PCBs), and Σ6 (NDL-PCBs) (analytical and TEQ cumulative concentrations, as appropriate). All the chemicals considered showed clear rates of a time-dependent concentration decrease, data having previously been adjusted for the sampled Region and subject age. Σ7 (PCDDs) exhibited the fastest decrease with an average rate of −4.44 pg/g-fat year −1 (2009–2018), whereas Σ6 (NDL-PCBs) was characterized by the slowest decrease with a rate of −0.771 ng/g-fat year −1 (2000–2018). A clear distinction between the decreasing rates of Σ7 (PCDDs) and Σ10 (PCDFs) was observed, as the latter decreased at half the rate of the Σ7(PCDDs). The slower rate of the Σ10 (PCDFs) decline may be due to an ongoing source of PCDFs in the environment beyond those traditionally considered for this group of contaminants such as the production of PCDFs due to PCBs thermal conversion from matrices contaminated with PCBs. Production of PCDFs due to thermal conversion of matrices contaminated with PCBs could be an ongoing source which may be of concern because recent data have highlighted the diffusion of PCBs in the European environment. The decreasing rates of PCDDs + PCDFs, DL-PCBs, and PCDDs + PCDFs + DL-PCBs — original analytical data converted to "dioxin equivalents" — were respectively estimated as (pgTEQ/g-fat year −1 ) −2.08, −2.06, and −2.10, values exhibiting good compatibility between one another. Graphical abstract: Image 1 Highlights: In many countries the decrease of legacy POPs concentrations has been reported. In Italy this decrease proceeds at comparable rates for "dioxin equivalents" data. The decrease proceeds at different rates for different chemical classes/families. There is a large difference between the decline in concentrations of the PCDDs and PCDFs. The PCB decreases is the slowest one.